Safety analysis of pipe string strength during transient process of ultrahigh temperature and high pressure well fracturing - Boyuan Yang; Hui Zhang; Kunhong Lv; Baokang Wu; Yuting Zhou; Xingyu Li; Ze Yang; Rui Yuan (Energy Science & Engineering)
Abstract With the continuous development of deep oil and gas resources, the number of high‐temperature and high‐pressure wells is increasing, and the complexity of fracturing operations is becoming more pronounced. The safe conduct of fracturing operations is crucial for improving production efficiency. To investigate the strength and safety of fracturing strings in high‐temperature and high‐pressure wells, a transient calculation model of temperature‐pressure coupling was established for fracturing strings in high‐temperature and high‐pressure wells. The safety factor method and triaxial stress analysis were employed to evaluate the safety of fracturing strings in high‐temperature and high‐pressure wells. The method was used to assess the fracturing strings in high‐temperature and high‐pressure wells, and the effects of fracturing fluid injection rate and string size on the stress of the strings were analyzed. The results indicate that the axial force and equivalent stress at the wellhead of the fracturing string are the highest; as the fracturing time and injection rate of the fracturing fluid increase, the axial stress and equivalent stress at the wellhead of the fracturing string also increase. Small‐sized pipes are conducive to improving the safety factor of fracturing pipe string operations. The research findings can provide theoretical guidance for designing fracturing strings for high‐temperature and high‐pressure wells.